2021
DOI: 10.1016/j.ijid.2021.02.073
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing SARS-CoV-2 genome diversity circulating in South American countries: Signatures of potentially emergent lineages?

Abstract: Objectives To evaluate the genomic diversity and geographic distribution of SARS-CoV-2 lineages currently circulating in South America (SA). Methods SARS-CoV-2 lineages reported from South American countries were analyzed from a public dataset of 5597 genome assemblies. Polymorphisms in the main open reading frames were identified and compared to those present in the main lineages of epidemiology concern: B.1.1.7 (from UK) and B.1.351 (from South Africa). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 11 publications
3
17
0
1
Order By: Relevance
“…The variant assignment results are expected because there was a predominance of the 20A and 20B (which includes the lineages B.1.1, B.1.1.274 and B.1.1.348) SARS-COV-2 variants circulating in South America (Camacho et al 2021; Muñoz et al 2021). The five different lineages (Table 1) found in this study are correlated with the clusters observed in the phylogenomic tree (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The variant assignment results are expected because there was a predominance of the 20A and 20B (which includes the lineages B.1.1, B.1.1.274 and B.1.1.348) SARS-COV-2 variants circulating in South America (Camacho et al 2021; Muñoz et al 2021). The five different lineages (Table 1) found in this study are correlated with the clusters observed in the phylogenomic tree (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…COVID-19 reinfections appear to be rare with very few cases confirmed by wholegenome sequencing reported globally to date [17]. Recently, the emergence of SARS-CoV-2 variants, such as the P.1 and the B.1.351, harboring a mutational repertoire within the Spike gene has raised concerns with regard to how this genetic variability may shape and modulate tissue tropism and potentially preclude the binding of neutralizing antibodies leading to a potential risk for reinfections, as recently reported [16][17][18][19]. Additionally, in a recent report, the immune plasma of COVID-19 convalescent blood donors had 6-fold less neutralizing capacity against the P.1 than against the B-lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient fully recovered after the second infection (no symptoms of chronic COVID-19 illness); yet, this case underscores the vulnerabilities of the host immune response when challenged by variants even between lineages descending from the same major lineage (B as in this case). The B lineage is the most prevalent major lineage circulating in South America [16]. Understanding this variability and the evolutionary dynamics of these emerging variants is pivotal for designing prevention strategies, such as vaccination campaigns, particularly in those countries where vaccination coverage is scarce, thus potentially setting the stage for other reinfection events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing vaccines may not be effective against some variants of severe acute respiratory syndrome coronavirus 2. However, vaccine uptake is still low in most countries, and we are not sure whether the available vaccines will be effective for the new variants or new ones that might come to eventually reach a herd immunity threshold ( 2 ).…”
mentioning
confidence: 99%